2023
DOI: 10.1101/2023.02.17.528979
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ergosterol distribution controls surface structure formation and fungal pathogenicity

Abstract: Ergosterol, the major sterol in fungal membranes, is critical for defining membrane fluidity and regulating cellular processes. Although ergosterol synthesis has been well defined in model yeast, little is known about sterol organization in the context of fungal pathogenesis. We identified a retrograde sterol transporter, Ysp2, in the opportunistic fungal pathogen Cryptococcus neoformans. We found that the lack of Ysp2 under host-mimicking conditions leads to abnormal accumulation of ergosterol at the plasma m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 70 publications
0
10
0
1
Order By: Relevance
“…Cells lacking this gene (ysp2Δ) accumulate ergosterol at the plasma membrane, leading to dramatic deformations of the membrane and cell wall. These mutant cells are also more sensitive than wild-type to the steroltargeting antifungal compound AmB and other membrane stressors 52 . To measure the response of this mutant to BRI and CAS, we performed MIC assays, using YNB medium because ysp2Δ cells grow extremely poorly in RPMI 52 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells lacking this gene (ysp2Δ) accumulate ergosterol at the plasma membrane, leading to dramatic deformations of the membrane and cell wall. These mutant cells are also more sensitive than wild-type to the steroltargeting antifungal compound AmB and other membrane stressors 52 . To measure the response of this mutant to BRI and CAS, we performed MIC assays, using YNB medium because ysp2Δ cells grow extremely poorly in RPMI 52 .…”
Section: Resultsmentioning
confidence: 99%
“…These mutant cells are also more sensitive than wild-type to the steroltargeting antifungal compound AmB and other membrane stressors 52 . To measure the response of this mutant to BRI and CAS, we performed MIC assays, using YNB medium because ysp2Δ cells grow extremely poorly in RPMI 52 . We found that the MIC for each compound was higher for ysp2Δ than for the corresponding wild-type, KN99a: 32 versus 8 µg/mL for CAS (Figure 2c) and 2.5 versus 1.25 µM for BRI (Figure 2d).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For quantification of morphology, a minimum of 94 cells from randomly-chosen slide coordinates were examined. For electron microscopy, cells were grown overnight in YPD or induced for 24 hours in DMEM before processing as in (48), except that the first incubation in 0.1 M sodium cacodylate buffer was performed for 2 h at RT. Supplemental Table S3.…”
Section: Imagingmentioning
confidence: 99%
“…In addition to thermotolerance, other aspects of the cactophilic lifestyle might be preadaptations for human pathogenicity. For instance, the sterol composition of the cell envelope has been implicated in fungal virulence 94,[116][117][118] . Mutations in genes involved in the ergosterol biosynthetic pathway are associated with antifungal resistance [118][119][120][121] , making it a major target of antifungal drugs 122 .…”
Section: Cactophily As a Launching Pad For The Emergence Of Opportuni...mentioning
confidence: 99%